Review—Pencil Graphite Electrodes as Platform for Enzyme and Enzyme-Like Protein Immobilization for Electrochemical Detection. Issue 3 (11th December 2019) - Nathani, Akash; Vishnu, Nandimalla; Sharma, Chandra S.
Abstract : Carbon-based electrodes are being used widely nowadays for biosensor applications, primarily owing to their good electrical conductivity and ease of functionalization. At the same time, the increasing demand for the low cost, disposable and the ease of availability for the do-it-yourself assemblies have provided an opportunity to look beyond conventional carbon materials for electrochemical analysis. In recent time, the pencil lead, entitled as the pencil graphite has been used as an electrode for the enzyme-based electrochemical biosensors. The review highlights the various aspects involved in using pencil graphite electrode (PGE) as a working electrode. This includes the various pretreatment strategies used, which is the first step toward the effective surface functionalization, followed by strategies used for the immobilization of the functional nanomaterials and the enzymes and finally, the integration of the PGE with different types of sensor assemblies. A comprehensive discussion on the latest development in this area also suggests future perspectives based on PGE to develop low-cost point-of-care diagnostics.